VALIANT CHILDREN OF OUR PEOPLE - Ubaydullayev Saidakbar Saydalievich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, information has been prepared about the heroism of our great allies, who loved and faithfully served their homeland, as well as the methods of overcoming the issues that are hindering the performance of combat missions (operations)and the development and application process of combat zinc by military personnel.